2
$\begingroup$

I solute this question like that and the question need to use the logic to proof that the first part implies the second part is true is my solute right or not , would appreciate any help.

\begin{align} \neg (p\wedge\neg Q) \vee Q & \implies \neg p \tag 1\\ \neg (p \vee Q) \wedge (\neg Q \vee Q) &\implies \neg p \tag 2 \\ \neg (p\wedge Q) &\implies \neg p \tag 3\\ \neg p \vee \neg Q &\implies ¬p \tag 4 \\ \end{align}

$\endgroup$
3
$\begingroup$

Examining a truth table shows you that something has to be wrong because if $p$ and $Q$ are both true, then the implication in $(1)$ is false.

The problem is when you go from statement $(1)$ to statement $(2)$. It looks like you're trying to distribute the conjunction across the disjunction but you haven't correctly handled the negation symbol.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.